LncRNA AWPPH inhibits SMAD4 via EZH2 to regulate bladder cancer progression. Issue 6 (27th February 2018) - Zhu, Feng; Zhang, Xinjun; Yu, Qinnan; Han, Guangye; Diao, Fengxia; Wu, Chunlei; Zhang, Yan
Abstract: This study aimed to investigate the effect and underlying mechanism of lncRNA AWPPH in bladder cancer (BC). A total of 20 Ta‐T1 stage BC tissues, 20 T2‐T4 stage BC tissues, and 20 normal bladder tissues, as well as human bladder epithelial cell line SV‐HUC‐1, human BC cell lines RT4, and T24 were obtained to detect the levels of AWPPH, enhancer of zeste homolog 2 (EZH2) and SMAD4 using RT‐qPCR or Western blotting. RT4 cells were transfected with pc‐AWPPH, pc‐EZH2, or pc‐control and T24 cells were transfected with si‐AWPPH, si‐EZH2, si‐control, or pc‐AWPPH + pc‐SMAD4, respectively. Then, cell proliferation, apoptosis, autophagy, and migration, were detected using MTT assay, colony formation assay, Annexin V‐FITC/PI method, Western blotting, and Transwell analysis, respectively. The relationship of AWPPH and EZH2 or SMAD4 was evaluated by RNA immunoprecipitation (RIP) assay or Chromatin immunoprecipitation (ChIP) assay. Compared with normal bladder tissues or cells, the levels of AWPPH and EZH2 were overexpressed, while SMAD4 was down‐regulated in BC tissues or cells (all P < 0.01). Cell viability, colony number, and migration were significantly increased, while cell apoptosis ratio was reduced in cells with pc‐AWPPH compared with cells with pc‐control (all P < 0.05), meanwhile, these effects were reversed by the treatment of pc‐SMAD4. Then, RIP assay revealed that AWPPH could bind to EZH2 and ChIP assay showed SMAD4 was regulated by EZH2. LncRNA AWPPH can promote cell proliferation, autophagy, and migration, as well as inhibit cell apoptosis in BC by inhibiting SMAD4 via EZH2. Abstract : This study aimed to investigate the effect and underlying mechanism of lncRNA AWPPH in bladder cancer (BC). RIP assay revealed that AWPPH could bind to EZH2, and ChIP assay showed SMAD4 was regulated by EZH2. LncRNA AWPPH can promote cell proliferation, autophagy, and migration, as well as inhibit cell apoptosis in BC by inhibiting SMAD4 via EZH2.